Karakteristik Wirausaha, Tingkat Pendidikan dan Karakteristik Usaha Sebagai Penentu Keberhasilan Bisnis Pariwisata di Wilayah Pesisir dan Pulau-Pulau Kecil - Fenri A. S. Tupamahu; Dessy Balik; Eduard Yohannis Tamaela (JURNAL MANEKSI, 2021)
This study aims to investigate the determinants of the success of the tourism business in coastal areas and small islands. This type of research is an exsplanatory study. The number of samples analyzed was 137 respondents, the sample selection in this study, using simple random sampling technique. Data analysis used descriptive analysis and inferential analysis. The findings of this study explain that, the entrepreneurial characteristics indicated in terms of, characteristics of faith, self-confidence, courageous, independent, persevering, aggressive, applicative, and open communication are proven to influence the success of the tourism business. This study reveals the findings that the level of education in terms of formal education, suitability of science and non-formal education has no real influence on the success of the tourism business. The results of the research prove that the characteristics of the business in terms of business origin, length of business, business scale, and characteristics of business operations have a positive effect on business success. The results also prove that entrepreneurial characteristics, education level and business characteristics influence simultaneously as a determinant of the success of tourism business in coastal areas and small islands.